The Role of Postoperative Imaging after Orbital Floor Fracture Repair. Issue 2 (June 2018) - Carpenter, David; Shammas, Ronnie; Honeybrook, Adam; Brown, C.Scott; Chapurin, Nikita; Woodard, Charles R.
Obtaining postoperative images of maxillofacial fractures does not affect the clinical management of asymptomatic patients; however, few studies have evaluated the role of postoperative imaging in the context of orbital floor fractures. In this study, we evaluate current practice techniques and the role of postoperative imaging in the management of orbital floor fractures in isolation and with concomitant facial fractures. Retrospective review of patients who underwent open reduction and internal fixation of orbital floor fractures between 2005 and 2015 at a single medical institution. Operative and perioperative records were reviewed to characterize postoperative imaging as routine or as indicated by concerning clinical symptoms, and to correlate clinical outcomes to postoperative imaging patterns across all identified orbital floor fractures. A total of 139 patients underwent open reduction and internal fixation of orbital floor fractures. Of these, 75 (54%) had zygomaticomaxillary (ZMC) involvement. The remaining 64 (46%) were isolated orbital floor fractures. Overall, 54 (39%) patients underwent postoperative imaging. Of these, 38 (70%) had postoperative imaging in the absence of concerning clinical symptoms. There was no observed difference in complication rates in those who underwent postoperative imaging, and those who did not. Patients with orbital + ZMC fractures underwent a significantly higher number of postoperative imaging studies ( p < 0.001); however, there was no observed difference in complications between isolated orbital and orbital + ZMC fractures. Routine postoperative imaging is not warranted in the absence of persistent clinical symptoms following open reduction and internal fixation of orbital floor fractures.